PENGGUNAAN AFIKSASI PADA BERITA MEDIA ONLINE RAKYATBENGKULU.COM DALAM HEADLINE POLITIK TAHUN 2024 - Kirani, Indah; Mahdijaya, Mahdijaya; Suyuthi, Hasmi; Gunawan, Hafiz (Universitas Sultan Ageng Tirtayasa, 2025)
In online media news content, especially in political headlines. Affixes can help readers understand the information they get from the news content. The formulation of this research problem is: how are the types of affixes used in rakyatbengkulu.com online media news in political headlines in 2024. The objectives of this research are: to describe the types and processes of using affixation in rakyatbengkulu.com online media news in political headlines in 2024, starting from September 04, 2024 to November 28, 2024. Based on the results of the research, the author found three types of affix use from four types of use, among others: 150 Prefixes, 33 suffixes and 242 confixes from 425 data found while infixes were not found in the news presented by rakyatbengkulu.com online media news in 2024 political headlines consisting of 30 political news that have been researched by the author.